The Role of Classroom Culture and Psychological Safety in EFL Students' Engagement - Tu, Xiaowei (Frontiers in Psychology, 2021)
Language learning is a complex phenomenon that is the outcome of an interplay of numerous inter/intra-personal variables. Out of these factors, emotions play a critical role in the whole process of learning. Research approves that positive emotions lead to positive outcomes. This is only obtainable in a positive classroom culture where students feel psychologically safe. If so, they actively engage in the classroom activities for a longer period. However, the macro-effect of classroom culture in EFL/ESL contexts has been limitedly explored. Against this shortcoming, the present article provides a brief account of the definition and conceptualization of classroom culture and its impact on two learner psychology variables (i.e., psychological safety, engagement). Moreover, the dimensions and factors influencing these variables are discussed. Finally, the study offers some implications for different stakeholders in EFL/ESL contexts and enumerates a number of research gaps and future directions for future scholars in this line of inquiry.